2001
DOI: 10.1046/j.1365-3083.2001.00840.x
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Forssman and Other Antigen/Antibody Systems in Vascularized Mouse Heart to Rat Xenotransplantation

Abstract: In the present study, the nature of hyperacute xenograft rejection was closely studied in a vascularized mouse-to-rat transplantation model. Antibodies against mouse heart, erythrocytes and lymphocytes and against the Forssman antigen were raised in the rat. Upon heterotopic heart transplantation the respective antisera were intravenously (i.v.) injected. Passive transfer of antiheart, antierythrocyte or antilymphocyte serum resulted in hyperacute rejection of the transplanted mouse heart. Subfractionation of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
7
0

Year Published

2002
2002
2012
2012

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 8 publications
(8 citation statements)
references
References 30 publications
1
7
0
Order By: Relevance
“…Some are probably also present on mouse blood cells because there are high titres of haemagglutinating and lymphocytotoxic antibodies present in the rat sera after rejection, as our previous study confirmed (14). Moreover, passive transfer of antierythrocyte or antilymphocyte sera shortly after transplantation induces hyperacute rejection (9). Thus, the mouse heart is believed to share antigens with mouse erythrocytes and with mouse lymphocytes.…”
Section: Discussionsupporting
confidence: 67%
See 1 more Smart Citation
“…Some are probably also present on mouse blood cells because there are high titres of haemagglutinating and lymphocytotoxic antibodies present in the rat sera after rejection, as our previous study confirmed (14). Moreover, passive transfer of antierythrocyte or antilymphocyte sera shortly after transplantation induces hyperacute rejection (9). Thus, the mouse heart is believed to share antigens with mouse erythrocytes and with mouse lymphocytes.…”
Section: Discussionsupporting
confidence: 67%
“…Some of the antigens relevant for the rejection process of a mouse‐to‐rat heart transplant are present on both mouse MNC and erythrocytes. Thus, hyperimmune sera from rats immunised with either cell type will induce hyperacute rejection when administered in conjunction with mouse heart transplantation (9). Nevertheless, more antigens of importance may exist because blood transfusions and extensive immunosuppression cannot induce humoral unresponsiveness in the mouse‐to‐rat model (10).…”
Section: Introductionmentioning
confidence: 99%
“…Adding CyA to the DSG treatment diminished the binding of antibodies to the grafts. By using haemagglutination assay and flow cytometry against mononuclear antigens as a measure of antibody response capable of inducing rejection [19], the low titres in the sera of all recipients of all six treatment groups were confirmed. Because of the DSG‐treated grafts having deposits of both IgM and IgG in the musculature on day 8 but not on day 2, the cell‐mediated rejection may also have an antibody component.…”
Section: Discussionmentioning
confidence: 99%
“…One suggestion is that the humoral unresponsiveness in concordant xenotransplantation is mediated by mechanisms occurring in the graft endothelium [9]. Furthermore, passive transfer of sera from rats immunized by transfusions with either mouse erythrocytes or lymphocytes leads to subsequent hyperacute rejection of a transplanted mouse heart [10]. These findings implicate the presence of important xenoantigens in mouse blood cells.…”
Section: Introductionmentioning
confidence: 99%